Efforts to Improve Student Learning Achievement by Applying the PAIKEM Learning Model for Islamic Religious Education Materials About Believing in Angels in Class IV Students of SDN No.171 / I Bajubang Laut, Muara Bulian District, Batang Hari Regency, 202 - Rahmah Rahmah; Weng Martin (At-Tasyrih: jurnal pendidikan dan hukum Islam, 2022)
The purpose of this study was to improve learning outcomes of fourth grade students through the PAIKEM learning model in the subject of Islamic Religious Education, the subject of faith in angels or Malaikah at IV SDN No. 171/I Bajubang Laut, Bajubang Laut Village, Muara Bulian District, Batang Hari Regency in even semesters, academic year 2020/2021. The method used in this research was Action Research which refers to the Classroom Action Research model consisting of two cycles which includes four stages; planning, action, observation, and reflection. Data analysis used quantitative and qualitative data. Analysis of quantitative data with descriptive statistics was to compare the results obtained from the first cycle and the second cycle, while the qualitative data analysis by analyzing data from the results of field notes and interviews during the study with steps. The results showed an increase in learning outcomes through the application of the PAIKEM learning model. This can be proven by the average score of completeness before the action was 60.21. The average test results of students during the learning process from cycle I to cycle II have increased. Student learning outcomes indicated by the scores they obtained in the evaluation tests of cycles I and II experienced a significant increase. In the first cycle, the students' completeness was only 67.67 to 80 in the second cycle.